Design and Stress Analysis of Face Gear Drive in Automobile - Sudhakar, S.Venkatesan, K.Hariharan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In automobiles, Gear drive failures are the major consequence which causes break downs; this can be optimized by newdevelopments in design, and stress analysis of gear drives. The main contents of the paper are: (i) identification of transmissionerrors for the reduction of noise, (ii) modifying the basic algorithm of tooth contact analysis, (iii) stress analysis of the modifiedfacegeardrive